Antioxidant food supplements in human health - Packer, Lester; Ed. Hiramatsu, Midori; Ed (Academic Press, 1999)
Discusses discoveries in the areas of oxygen and nitric oxide metabolism and pathophysiology, redox regulation and cell signaling, and the identification of natural antioxidants and their mechanisms of action on free radicals and their role in health and disease. This work is useful for researchers and professionals in food science and nutrition.